2022
DOI: 10.3390/f14010021
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Microbial Communities under Mixed Organic and Inorganic Nitrogen Addition in Temperate Forests

Abstract: Investigating the response of soil microbial communities to nitrogen (N) deposition is critical to understanding biogeochemical processes and the sustainable development of forests. However, whether and to what extent different forms of N deposition affect soil microbial communities in temperate forests is not fully clear. In this work, a field experiment with three years of simulated nitrogen deposition was conducted in temperate forests. The glycine and urea were chosen as organic nitrogen (ON) source, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…While NH 4 NO 3 is often utilized in N addition studies due to convenience and ease of comparison to past research, it is less representative of atmospheric deposition to natural ecosystems (Erisman and De Vries, 2000). N form has been reported to affect the diversity and composition of microbial communities (Liu et al, 2021;Ding et al, 2023). It has been suggested that NH 4 + plays an important role in shaping bacterial but not fungal communities based on a study of temperate forest soil (Ding et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While NH 4 NO 3 is often utilized in N addition studies due to convenience and ease of comparison to past research, it is less representative of atmospheric deposition to natural ecosystems (Erisman and De Vries, 2000). N form has been reported to affect the diversity and composition of microbial communities (Liu et al, 2021;Ding et al, 2023). It has been suggested that NH 4 + plays an important role in shaping bacterial but not fungal communities based on a study of temperate forest soil (Ding et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…N form has been reported to affect the diversity and composition of microbial communities (Liu et al, 2021;Ding et al, 2023). It has been suggested that NH 4 + plays an important role in shaping bacterial but not fungal communities based on a study of temperate forest soil (Ding et al, 2023). This is an important consideration given that bacteria tend to dominate over fungi in biomes with high mean annual temperature and net primary productivity, such as tropical regions (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Actinobacteriota at a depth of 0-20 cm was significantly higher in hummock compared to flat and hollow soil, potentially due to the presence of woody shrubs (Vaccinium uliginosum and Rhododendron tomentosum) [46]. Acidobacteriota members are generally oligotrophic and many prefer nutrient-poor environments [47]. Our observations showed that the relative abundance of Acidobacteriota was lower at a depth of 20-40 cm, where organic carbon content was higher compared to 0-20 cm and 40-60 cm, which is consistent with the results of Xiao et al [48].…”
Section: Changes In Microbial Community Structures In Different Posit...mentioning
confidence: 99%
“…Considering that the soil in drylands is characterized by water deficit, loose structure, and severe salinization, belowground processes, including microbial activity and community dynamics, biogeochemical cycling, and soil respiration, interact to affect many aspects of plant growth state and ecosystem function these areas. Based on the changes in soil microbial communities under mixed inorganic and organic nitrogen addition in temperature forests, the study by Ding et al [1] suggested that different components of nitrogen deposition need to be considered when studying the effects of nitrogen deposition on soil microorganisms in terrestrial ecosystems. Along an urban-rural environment gradient, Shen et al [2] found that pH, organic matter, and ammonium nitrogen were the main driving factors of the differences in soil ectomycorrhizal fungi community composition and diversity in oak forests.…”
mentioning
confidence: 99%